2013
DOI: 10.1177/0013916513515239
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Beliefs About Bottled Water and Intentions to Reduce Consumption

Abstract: Mass consumption of bottled water is contributing to a multitude of environmental problems, including water wastage, pollution, and climate change. The aim of this study is to advance a social-psychological understanding of how to effectively reduce bottled water consumption. An online survey experiment was conducted among students of a Dutch public university to explore outcome beliefs about drinking less bottled water while testing three strategies for behavioral change. Respondents (N = 454) were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 72 publications
(89 reference statements)
5
27
0
3
Order By: Relevance
“…These are different from some developed countries and some wealthy city in China. Bottled or barreled water consumption in these areas has greatly increased in the past decade [22,23]. Based on 2016 Hainan Environmental Status Bulletin, the water quality of surface water and ground water is good, and the qualified rate of water quality of surface water is 90.1% (and is considered as excellent by local authorities, which can be questioned), and there are not many accidental water pollution events in Hainan province except flooding and typhoons [24].…”
Section: Household Drinking Water Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are different from some developed countries and some wealthy city in China. Bottled or barreled water consumption in these areas has greatly increased in the past decade [22,23]. Based on 2016 Hainan Environmental Status Bulletin, the water quality of surface water and ground water is good, and the qualified rate of water quality of surface water is 90.1% (and is considered as excellent by local authorities, which can be questioned), and there are not many accidental water pollution events in Hainan province except flooding and typhoons [24].…”
Section: Household Drinking Water Sourcesmentioning
confidence: 99%
“…A few respondents used barreled or bottled water as their main household drinking water sources. Some studies have shown that when consumers are dissatisfied with the tap water provided by municipalities they often turn to bottled or barreled water [22,23]. Barreled and bottled water quality is regulated by the China Food and Drug Administration, but many local residents are peasants or fishermen who are not wealthy, thus, relatively expensive barreled or bottled water is not commonly purchased and used.…”
Section: Household Drinking Water Sourcesmentioning
confidence: 99%
“…There have been numerous information-based initiatives that have attempted to change behaviors that can generate negative social spillovers, such as excessive alcohol consumption, drug use, gambling, and littering [5]. Other studies have shown that information campaigns can be effective in promoting environmental conservation behavior, such as reduced water use [5][6][7][8], reduced bottled water consumption [9], increased re-use of hotel towels [10], reduced electric energy consumption [1,11], and increased sustainable transportation behavior [12].…”
Section: Of 10mentioning
confidence: 99%
“…If reducing nonsustainable consumption behaviour is a goal, future research should seek to identify how the perceived benefits of bottled water identified in this study could be reframed and mitigated in marketing communications. To date, only van der Linden has undertaken research as to how this might occur, with his research suggesting that the dual effect of activating social norms and providing persuasive information has the most impact on decreasing intentions to purchase bottled water [54].…”
Section: Discussionmentioning
confidence: 99%